Model for Nonrelativistic Topological Multiferroic Matter - Allende-Prieto, S; Castro-Barrera, M (American Physical Society, 2023)
We provide a model capable of accounting for the multiferroicity in certain materials. The model s base is on free electrons and spin moments coupled within nonrelativistic quantum mechanics. The synergistic interplay between the magnetic and electric degrees of freedom that turns into the multiferroic phenomena occurs at a profound quantum mechanical level, conjured by Berry s phases and the quantum theory of polarization. Our results highlight the geometrical nature of the multiferroic order parameter that naturally leads to magnetoelectric domain walls, with promising technological potential. © 2023 American Physical Society.